Analisis Sistematis Strategi Pembelajaran Inkuiri terhadap Pengembangan Keterampilan Abad 21 - Lailatul Zulfa; Hasan Fauzi; Rahmat Kamal (Badan Penerbit STIEPARI Press, 2025)
21st century education demands the development of essential skills such as critical thinking, creativity, collaboration, and communication. Inquiry learning strategies, which focus on students' active involvement in the exploration and investigation process, are one of the relevant approaches to address these challenges. This study aims to identify integration patterns and contributions of inquiry learning strategies to the development of 21st century skills that are trending research references and challenges in their implementation through the Systematic Literature Review (SLR) method. The literature was collected from scientific databases such as Scopus, ERIC, and Google Scholar, with a publication period between 2016–2024. The results of the analysis of 21 selected articles showed that inquiry strategies have integration patterns in guided inquiry, problem-based learning (PBL), and project-based learning (PjBL) learning models, contributing to developing analytical thinking patterns, freedom to explore, training teamwork, and fluent interaction. Inquiry is an adaptive strategy in various learning contexts, but systemic and technical obstacles are still found in its implementation.